MOSFET-only multi-function biquad filter - (:unkn) unknown (ELSEVIER GMBH, URBAN & FISCHER VERLAG, 2015)
In this paper, using only seven MOS transistors, second order current-mode LP/BP filter is proposed. The transconductances of the MOS transistors in saturation region are used instead of passive resistors and gate-to-source capacitances are employed instead of passive capacitors. The proposed circuit exhibits important features such as simplicity, reduced chip area and wide frequency range compared to classical analog circuits that require active elements including large number of transistors. Layout of the proposed circuit is drawn using Mentor Graphics IC Station layout editor. AMS 0.35 mu m process parameters are used during post-layout simulations. (C) 2015 Elsevier GmbH. All rights reserved.
Keywords: Active filter; Current-mode; Low-voltage; Low-power; MOSFET-only; ALLPASS FILTERS; PASS FILTER; TRANSISTOR; REALIZATION